Accuracy of cup placement compared with preoperative surgeon targets in primary total hip arthroplasty using standard instrumentation and techniques: a global, multicenter study - Geert Meermans; David Fawley; Luigi Zagra; René H. M. ten Broeke; Kory Johnson; Thierry Bernard; Henry Clayton Thomason (Journal of Orthopaedics and Traumatology, 2024)
Abstract Background Acetabular cup positioning in total hip arthroplasty (THA) is closely related to outcomes. The literature has suggested cup parameters defined by the Lewinnek safe zone; however, the validity of such measures is in question. Several studies have raised concerns about the benefits of using the Lewinnek safe zone as a predictor of success. In this study we elected to use prospective surgeon targets as the basis for comparison to see how successful surgeons are positioning their cup using standard instruments and techniques. Methods A prospective, global, multicenter study was conducted. Cup positioning success was defined as a composite endpoint. Both cup inclination and version needed to be within 10° of the surgeon target to be considered a success. Radiographic analysis was conducted by a third-party reviewer. Results In 170 subjects, inclination, target versus actual, was 44.8° [standard deviation (SD 0.9°)] and 43.1° (SD 7.6°), respectively (p = 0.0029). Inclination was considered successful in 84.1% of cases. Mean version, target versus actual, was 19.4° (SD 3.9°) and 27.2° (SD 5.6°), respectively (p < 0.0001). Version was considered successful in 63.4% of cases, and combined position (inclination and version) was considered successful in 53.1%. Conclusion This study shows that with traditional methods of placing the cup intraoperatively, surgeons are only accurate 53.1% of the time compared with a predicted preoperative plan. This study suggests that the inconsistency in cup positioning based on the surgeon’s planned target is potentially another important variable to consider while using a mechanical guide or in freehand techniques for cup placement in THA. Trial Registration: This study is registered on ClinicalTrials.gov, NCT03189303.